A retrospective cohort study: pre‐operative oral enteral nutritional optimisation for Crohnʼs disease in a UK tertiary IBD centre. Issue 4 (20th June 2022) - Meade, Susanna; Patel, Kamal V.; Luber, Raphael P.; O'Hanlon, Dearbhaile; Caracostea, Andra; Pavlidis, Polychronis; Honap, Sailish; Anandarajah, Cheran; Griffin, Nyree; Zeki, Sebastian; Ray, Shuvra; Mawdsley, Joel; et al.
Summary: Background: Low‐quality evidence suggests that pre‐operative exclusive enteral nutrition (E/EN) can improve postoperative outcomes in patients with Crohn's disease (CD). It is not standard practice in most centres. Aims: To test the hypothesis that pre‐operative EN in patients undergoing ileal/ileocolonic surgery for CD is associated with improved postoperative outcome. Methods: We performed a single centre retrospective observational study comparing surgical outcomes in patients receiving pre‐operative EN (≥600 kcal/day for ≥2 weeks) with those who received no nutritional optimisation. Consecutive adult patients undergoing ileal/ileocolonic resection from 2008 to 2020 were included. The primary outcome was postoperative complications <30 days. Secondary outcomes included EN tolerance, specific surgical complications, unplanned stoma formation, length of stay, length of bowel resected, readmission and biochemical/anthropometric changes. Results: 300 surgeries were included comprising 96 without nutritional optimisation and 204 optimised cases: oral EN n = 173, additional PN n = 31 (4 of whom had received nasogastric/nasojejunal EN). 142/204 (69.6%) tolerated EN. 125/204 (61.3%) initiated EN in clinic. Patients in the optimised cohort were younger at operation and diagnosis, with an increased frequency of penetrating disease and exposure to antibiotics or biologics, and were more likely to undergo laparoscopic surgery. The optimised cohort had favourable outcomes on multivariate analysis: all complications [OR 0.29; 0.15–0.57, p < 0.001], surgical complications [OR 0.41; 95% CI 0.20–0.87, p = 0.02], non‐surgical complications [OR 0.24 95% CI 0.11–0.52, p < 0.001], infective complications [OR 0.32; 95% CI 0.16–0.66, p = 0.001]. Conclusions: Oral EN was reasonably well tolerated and associated with a reduction in 30‐day postoperative complications. Randomised controlled trials are required to confirm these findings. Abstract : Low‐quality evidence suggests that pre‐operative exclusive enteral nutrition (E/EN) can improve postoperative outcomes in patients with Crohn's disease (CD). It is not standard practice in most centres. We performed a retrospective observational study to test the hypothesis that pre‐operative EN in patients undergoing ileal/ileocolonic surgery for CD is associated with improved postoperative outcome. Consecutive adult patients undergoing ileal/ileocolonic resection from 2008 to 2020 were included. The primary outcome was postoperative complications within 30‐days. Secondary outcomes included EN tolerance, specific surgical complications, unplanned stoma formation, length of stay, length of bowel resected, readmission and biochemical/anthropometric changes. We have demonstrated that oral EN was reasonably well tolerated (69.6% achieved EN and 61.3% achieved EEN) and its use was associated with a reduction in 30‐day postoperative complications. Prospective randomised controlled trials are required to confirm these findings.